Análisis de la transmisión de datos y seguridad de la red de proveedor de internet en la empresa cybermar en el recinto Mata de Cacao - Garcia Garcia, Edison Fernando (2019)
CYBERMAR is a company that sells internet (ISP), in addition to selling stationery, and short-term computer rental, in addition to conducting research, the company is located in the Mata de Cacao Campus, Babahoyo Canton, Los Ríos Province. In this case study the traffic and security of the network in the company will be analyzed, since one of the problems that the company has is slow internet service at certain times in the client, in addition to lack of security in their equipment of administration. In this project, the observation methodology was carried out by performing inspection in the Internet transmission towers, using tools such as surveys directed at the owner manager and certain clients, also using analysis techniques. The limitation of this research project is based on the case study to analyze the data transmission and security of the CYBERMAR company network in the Mata de Cacao Campus